Challenging Gender Boundaries in Youth Cinema: A Feminist Analysis of Enola Holmes - Assidiqi, Hasbi Muhamad; Muttaqien, Muhammad Zainal (Morphosis: Journal of Literature, 2025)
This research examines the portrayal of gender boundaries in youth films, specifically focusing on Enola Holmes, directed by Harry Bradbeer. Using a qualitative-descriptive method, this study emphasizes the process and meaning embedded in the film’s narrative and character development. Through this approach, the research identifies key themes related to gender limitations, feminism, and gender stereotypes, all of which contribute to the film’s broader social commentary. One of the central discussions in this study is the depiction of gender boundaries and how they are challenged within the film. Enola Holmes presents a strong female protagonist who defies traditional gender expectations, positioning herself as an independent and capable individual in a society that often marginalizes women. The film highlights the struggles women face in their fight for equality, showcasing how female characters challenge the patriarchal norms that seek to limit their roles and opportunities. Additionally, Enola Holmes incorporates feminist themes that align with contemporary discussions on gender equality. The protagonist’s journey is not only one of self-discovery but also of resistance against societal norms that attempt to confine her based on gender. This is particularly evident in how Enola navigates the expectations placed upon her as a young woman in Victorian England, refusing to conform to the passive and domestic roles traditionally assigned to women. Another significant aspect of this analysis is the exploration of gender stereotypes. The film subverts traditional portrayals of female characters by presenting Enola as intelligent, resourceful, and determined—qualities often attributed to male protagonists in adventure and detective genres. Her character challenges the notion that women are inherently weaker or less capable than men, emphasizing the importance of breaking free from societal constraints. Overall, Enola Holmes serves as an engaging case study for examining gender representation in youth films. By challenging traditional gender roles and advocating for female empowerment, the film contributes to a broader discourse on gender equality. This research underscores the significance of media in shaping and reflecting societal attitudes toward gender, making Enola Holmes a compelling subject for academic analysis.